CHINESE ACTIVE LIFESTYLE DEVELOPMENT: LIMITATIONS AND COUNTERMEASURES - Zhou,Jun (2022)
ABSTRACT Objective: To analyze the reality of the development of the national active lifestyle, clarify its limitations and countermeasures. Methodology: Official data and consultations in updated bibliographic references were employed for the survey of the main problems with a sedentary lifestyle and their possible solutions. Results: The three urgent problems to be solved in public services are the construction of sports facilities, the organization of regular sports activities, and the establishment of sports organizations. Only a few sports have been promoted in concrete operations. Inadequate physical education and deficient essential public services are also factors affecting national health. Conclusion: Building sports facilities and providing environments with sports equipment are not sufficient against sedentary lifestyles. Relevant policies must be implemented along with massive advertising about the benefits of active lifestyles. Continuous orientation of social workers in community sports groups to promote mass participation is also key to health promotion through sports interventions.